Strengthening MSME Marketing through Digital Marketing and Financial Management Training: International Community Service in Cianjur, West Jawa - Umiyati, Hesti; Tribuana, Dhimas; Hermawan, Budi; Suherman, Eman; Triyanto, Dedi; Dewi, Puri Swastika Gusti Krisna; Whardani, Kristina Whardani (MOVE: Journal of Community Service and Engagement, 2025)
This international community service, organized by the Doctoral Students of the Management Science Doctoral Program, Class of 2023, at UNIKOM, aimed to enhance the marketing and managerial capabilities of Micro, Small, and Medium Enterprises (MSMEs) affiliated with the Bumi Cianjur Cooperative in West Java. Conducted on February 16–17, 2025, the event was attended by 10 MSMEs operating in various sectors, including services, consumer goods, marketing, production, and savings and loans. The activities included an MSME product exhibition, digital marketing training, financial management workshops, and business consultations. Distinguished speakers from both Indonesia and abroad contributed to the program. The results showed improvements in the participants’ understanding of digital marketing strategies and financial planning, contributing to increased business sustainability and competitiveness. This initiative demonstrates the value of academic-community collaboration and the role of higher education in empowering local enterprises through international engagement.